Mapping the Assembly of Metal–Organic Cages into Complex Coordination Networks. Issue 72 (30th November 2017) - Yadav, Ashok; Gupta, Arvind K.; Steiner, Alexander; Boomishankar, Ramamoorthy
Abstract: Structural transformations of supramolecular assemblies play an important role in the synthesis of complex metal–organic materials. Nonetheless, often little is known of the assembly pathways that lead to the final product. This work describes the conversion of cubic metal–organic polyhedra to connected‐cage networks of varying topologies. The neutral cubic cage assembly of formula Pd3 [PO(N i Pr)3 ]8 (PZDC)12 has been synthesized from Pd3 [(N i Pr)3 PO](OAc)2 (OH)2 ⋅2 (CH3 )2 SO and 2, 5‐pyrazenedicarboxilic acid (PZDC‐2H). This 42‐component self‐assembly is the largest known among the neutral cages with Pd II ions. The cage contains twenty‐four vacant carboxylate O‐sites at the PZDC ligands that are available for further coordination. Post‐assembly reactions of the cubic cage with Fe II and Zn II ions produced cage‐connected networks of dia and qtz topologies, respectively. During these reactions, the discrete cubic cage transforms into a network of tetrahedral cages that are bridged by the 3D metal ions. The robustness of the [Pd3 [PO(N i Pr)3 ] 3+ molecular building units made it possible to map the post‐assembly reactions in detail, which revealed a variety of intermediate 1D and 2D cage networks. Such step‐by‐step mapping of the transformation of discrete cages to cage‐connected frameworks is unprecedented in the chemistry of coordination driven assemblies. Abstract : Fusion of cubes : Conversion of a cubic metal–organic polyhedron to connected‐cage 3D‐networks of varying topologies is reported. Structural characterization of various 1D‐ and 2D‐intermediate assemblies unfolds a fully mapped pathway for these conversions.